The psychological impact of COVID-19 infection on athletes: example of professional male football players - Lima, Y.; Denerel, N.; Yilmaz, N. D.; Senisik, S. (Science and Medicine in Football, 2021)
Objective: The purpose of this study was to evaluate the psychological state of professional male football players who were infected by COVID-19. Method: The Depression Anxiety Stress Scale 21 and Kessler Psychological Distress Scale were sent to players` smartphones by sharing a link to the questionnaire. A total of 523 professional football players aged between 18-38 years from 93 different sports clubs participated in the study. The players were divided into 2 groups according to Sars-COV-2 PCR test results. Results: Depression, anxiety, stress, and psychological distress scores of football players who were infected by COVID-19 were higher compared to players who were not infected by COVID-19 (all p < 0.001). Depression, stress, and psychological distress scores were higher for football players with higher loss of income than players with lower loss of income (p = 0.017, p = 0.007, p = 0.005, respectively). There were significant differences in anxiety, depression, and psychological distress scores in favor of the 18-22-year age group (p = 0.002, p = 0.009, p = 0.004, respectively). Conclusion: COVID-19 infection negatively affects the psychological states of football players. The psychological states of professional football players who were infected by COVID-19 should be monitored closely and psychological support should be provided.